Male soy food intake was not associated with in vitro fertilization outcomes among couples attending a fertility center. (20th June 2015) - Mínguez‐Alarcón, L.; Afeiche, M. C.; Chiu, Y.‐H.; Vanegas, J. C.; Williams, P. L.; Tanrikut, C.; Toth, T. L.; Hauser, R.; Chavarro, J. E.
Summary Male factor etiology may be a contributing factor in up to 60% of infertility cases. Dietary intake of phytoestrogens has been related to abnormal semen quality and hormone levels. However, its effect on couple fecundity is still unclear. Intake of soy products was assessed in 184 men from couples undergoing infertility treatment with in vitro fertilization. Couples were recruited between February 2007 and May 2014 and prospectively followed to document treatment outcomes including fertilization, implantation, clinical pregnancy and live birth. Multivariate generalized linear mixed models with random intercepts, binomial distribution and logit link function were used to examine this relation while accounting for repeated treatment cycles and adjusting for potential confounders. Male partner's intake of soy foods and soy isoflavones was unrelated to fertilization rates, the proportions of poor quality embryos, accelerated or slow embryo cleavage rate, and implantation, clinical pregnancy and live birth. The adjusted live birth rates per initiated cycle (95% CI) for partners of men in increasing categories of soy food intake were 0.36 (0.28–0.45), 0.42 (0.29–0.56), 0.36 (0.24–0.51), and 0.37 (0.24–0.52), respectively. Soy food intake in men was not related to clinical outcomes among couples presenting at an infertility clinic. Data on the relation between phytoestrogens and male reproductive potential remain scarce and additional research is required to clarify its role in human reproduction.